2010
DOI: 10.1029/2009jd013410
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of high‐precipitation events in Dronning Maud Land, Antarctica

Abstract: [1] High-resolution Antarctic Mesoscale Prediction System archive data were used to investigate high-precipitation events at the deep ice core drilling site Kohnen Station, Dronning Maud Land, Antarctica, during the period [2001][2002][2003][2004][2005][2006]. The precipitation is found to be highly episodic, with, on average, approximately eight high-precipitation events per year that can bring more than half of the total annual accumulation. The duration of the events varies between 1 day and about 1 week. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
149
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(164 citation statements)
references
References 41 publications
7
149
0
Order By: Relevance
“…Earlier studies have shown that episodic precipitation events very often occur together with increases in wind speed and temperature (e.g., Birnbaum et al, 2010;Fujita and Abe, 2006;Schlosser et al, 2008Schlosser et al, , 2010. Birnbaum et al (2010) showed in Fig. 6 of their paper a time series of daily precipitation rates from AMPS forecasts for 2002, together with periods identified as strong-wind events on the basis of the 2 hour mean values of wind speed measured at the AWS at EPICA DML.…”
Section: Processes Related To Smbmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies have shown that episodic precipitation events very often occur together with increases in wind speed and temperature (e.g., Birnbaum et al, 2010;Fujita and Abe, 2006;Schlosser et al, 2008Schlosser et al, , 2010. Birnbaum et al (2010) showed in Fig. 6 of their paper a time series of daily precipitation rates from AMPS forecasts for 2002, together with periods identified as strong-wind events on the basis of the 2 hour mean values of wind speed measured at the AWS at EPICA DML.…”
Section: Processes Related To Smbmentioning
confidence: 99%
“…Therefore, the role of wind is also one of the keys to better understand the SMB. Earlier studies have shown that episodic precipitation events very often occur together with increases in wind speed and temperature (e.g., Birnbaum et al, 2010;Fujita and Abe, 2006;Schlosser et al, 2008Schlosser et al, , 2010. Birnbaum et al (2010) showed in Fig.…”
Section: Processes Related To Smbmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have confirmed and extended these results for different parts of Antarctica. For example, it has been shown that a few snowfall events per year can be responsible for up to half of the annual total precipitation (Braaten, 2000;Reijmer and Van den Broeke, 2003;Fujita and Abe, 2006;Schlosser et al, 2010a;Gorodetskaya et al, 2013). In addition, Gorodetskaya et al (2014) showed that atmospheric rivers play an important role in heavy precipitation events in Antarctica.…”
Section: Synoptic Analysismentioning
confidence: 99%
“…Bromwich et al, 2005Bromwich et al, , 2013Deb et al, 2016), while model output from AMPS has supported various Antarctic investigations (e.g., Powers, 2007;Nigro et al, 2011Nigro et al, , 2012. The AMPS archive is the repository of gridded output from AMPS from over the years (Powers et al, 2012), and WRF gridded output from the archive has supported numerous studies Cassano, 2008, 2012;Schlosser et al, 2010aSchlosser et al, , 2016. Here, AMPS archive data from the period 2008-2010 are used here in analyses of the meteorological conditions affecting Dome C and its precipitation.…”
Section: Antarctic Mesoscale Prediction System (Amps)mentioning
confidence: 99%